PENGANGGARAN BERBASIS KINERJA DAN KEJELASAN SASARAN ANGGARAN TERHADAP AKUNTANBILITAS KINERJA PEMERINTAH DAERAH - Amaliya, Mifta (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2022)
ABSTRACT This study aims to see the effect of performance-based budgeting and clarity of budget targets on the local government performance accountability system, the internal control system as an intervention variable. The dependent variable used in this study is the Local Government Performance Accountability System. Meanwhile, the independent variables are Performance-Based Budgeting and Clarity of Budget Targets. The Intervening variable used is the Internal Control System. The population in this study are all employees who contribute to financial management and budgeting, which may have been 90 people in the Regional Financial and Revenue Management Agency (BPKPD). The sample in this study using convenience sampling. The analysis used in this study is to use path analysis. Based on the research results it can be said that: (1) there is a positive and significant effect of performance budgeting on performance accountability; (2) there is a positive and significant effect of clarity of budget targets on performance accountability; (3) there is no significant influence on the performance accountability internal control system; (4) there is a positive and significant influence on the internal control system performance budgeting; (5) there is a positive and significant effect on the clarity of the internal control system objectives; (6) there is no effect of budgeting on the accountability performance of the internal control system performance; (7) there is no effect of budget clarity on the accountability of the internal control system performance. Keywords: Performance-Based Budgeting, Clarity of Budget Objectives, Internal Control Systems, Performance Accountability.